Cross-institutional knowledge-based planning (KBP) implementation and its performance comparison to Auto-Planning Engine (APE). Issue 1 (April 2017) - Wu, Binbin; Kusters, Martijn; Kunze-busch, Martina; Dijkema, Tim; McNutt, Todd; Sanguineti, Giuseppe; Bzdusek, Karl; Dritschilo, Anatoly; Pang, Dalong
Abstract: Background and purpose: To investigate (1) whether a plan library established at one institution can be applied for another institution's knowledge-based planning (KBP); (2) the performance of cross-institutional KBP compared to Auto-Planning Engine (APE). Material and methods: Radboud University Medical Center (RUMC) provided 35 oropharyngeal cancer patients (68 Gy to PTV 68 and 50.3 Gy to PTV 50.3 ) with clinically-delivered and comparative APE plans. The Johns Hopkins University (JHU) contributed a three-dose-level plan library consisting of 179 clinically-delivered plans. MedStar Georgetown University Hospital (MGUH) contributed a KBP approach employing overlap-volume histogram (OVH-KBP), where the JHU library was used for guiding RUMC patients' KBP. Since clinical protocols adopted at RUMC and JHU are different and both approaches require protocol-specific planning parameters as initial input, 10 randomly selected patients from RUMC were set aside for deriving them. The finalized parameters were applied to the remaining 25 patients for OVH-KBP and APE plan generation. A Wilcoxon rank-sum test was used for statistical comparison. Results: PTV 68 and PTV 50.3 's V 95 in OVH-KBP and APE were similar ( p  > 0.36). Cord's D 0.1 cc in OVH-KBP was reduced by 5.1 Gy ( p  = 0.0001); doses to other organs were similar ( p  > 0.2). Conclusion: APE and OVH-KBP's plan quality is comparable. Institutional-protocol differences can be addressed to allow cross-institutional library sharing.